Renewable and sustainable biobased materials: An assessment on biofibers, biofilms, biopolymers and biocomposites - Vinod, A.; Sanjay, M.R.; Suchart, Siengchin; Jyotishkumar, Parameswaranpillai (Journal of cleaner production, 2020)
The current global scenario has a great impact on the development of new bio-based materials due to its vital advantages that are helpful in replacing synthetic and hazardous materials. This perspective review presents the advancement in the processing techniques, characterizations, future scope and methods to overcome the limitations in biofibers, biopolymers, biofilms, and bio composites. This provides vital information on advanced bio-based materials and its composites for their potential usage in biomedical, commercial and engineering sectors to the researchers and scientists. The usage of bio-based materials that are renewable in the field of constructions and engineering will improve the sustainability by reducing wastages, landfills and toxic emissions leading to greener and cleaner environment. •Comprehensive review on the various aspects of eco-friendly biobased materials.•Replacement for synthetic materials in the concern of environmental awareness.•Recent improvements in biofibers, biopolymers, biofilms and biocomposites.•Outline of the importance of biobased materials for various applications.